Effect of Population Density and Urban Intensity on Building Typology in South Krembangan Area - Puspita, Cindy; Dharmatanna, Stephanus Wirawan (Journal of Architectural Design and Urbanism, 2023)
Surabaya is the second largest city in Indonesia and is part of East Java. Surabaya has a strategic location and was utilized by the Dutch Colonial Government as one of the main ports. The Kalimas River served as the trading artery of Surabaya. Surabaya was broadly divided into three dominant areas: the European district, the Chinatown district, and the Arab district, all of which are delineated by the Kalimas River. Krembangan Selatan Village is of particular interest for research due to the presence of many colonial-style buildings and the shift from a historical trading area to a residential area.  To understand the influence of population density and urban intensity on building typology, a qualitative descriptive analysis was conducted by observing building typology and the year of construction which helped in determining how population density and intensity affect building typology in the Krembangan Selatan area. Urban Intensity was assessed by calculating the building volume divided by 300. The highest intensity group consists of residential areas with buildings in a typical style of the 1960s. Density calculations were made by comparing the area to Semarang, as both areas were influenced by the Dutch colonial Government.  This occurred because Semarang's Old Town area still maintains its urban tissue as a historical area dominated by public buildings, in contrast to Krembangan Selatan, which is dominated by service providers, educational facilities, and residential buildings.